PERAN PARTAI DEMOKRASI I INDONESIA PERJUANGAN DALAM MEMENANGKAN PASANGAN GANJAR PRANOWO - HERU SUDJATMOKO PADA PILGUB JATENG 2013 - Utomo, Susilo (JURNAL ILMU SOSIAL, 2015)
This study intends investigate the role of PDI in winning pair Ganjar Pranowo-Heru Sudjatmoko in Central Java Governor Election 2013. The research method uses a qualitative approach, in-depth interviews with key figures Success Team Couple Ganjar- Heru. The results show that the role of PDI was very decisive in determining the victory of the Central Java Governor Election 2013. Political Role of the PDI-P that took the role asÂ  political recruiter and as an engine pollster orÂ  mass mobilization.